Kompetensi Manajerial Kepala Madrasah Dalam Meningkatkan Profesionalisme Guru di MTsN 4 Aceh Tenggara - Ramlan Ramlan (IHSANIKA : Jurnal Pendidikan Agama Islam, 2023)
This research aims to: (1) describe the managerial competence of madrasa heads in increasing teacher professionalism at MTsN 4 Aceh Tenggara. (2) describe the factors that support and also hinder madrasa heads in increasing teacher professionalism at MTsN 4 Aceh Tenggara. This research uses a descriptive qualitative approach. Data collection techniques using observation, interviews and documentation methods. Data analysis techniques: (1) data reduction, (2) data presentation, and (3) drawing conclusions. The research subjects are the Madrasa Head, teachers and curriculum representatives. The results of this research are (1) the managerial competence of madrasa heads in increasing teacher professionalism at MTsN 4 Southeast Aceh is carried out using technical skills, humanity skills and conceptual skills. Namely by providing motivation, appreciation and coordinating teachers to take part in training, providing facilities and infrastructure. (2) factors that support and also hinder madrasa heads in increasing teacher professionalism at MTsN 4 Aceh Tenggara. (a) supporting factors such as: teacher education, good cooperation, participation in scientific work, salary provision. (b) inhibiting factors such as: lack of advice and infrastructure, curriculum changes, not understanding the curriculum, not being disciplined in madrasa regulations, and the teacher's residence being far away. The madrasa head must be able to manage his subordinates in carrying out their duties. The managerial competence of madrasah heads has a complementary relationship with each other and the teacher's performance in asking for opinions or suggestions from subordinates when making every decision when holding activities so that there is a reciprocal relationship and a harmonious bond is established between superiors and subordinates which influences their professionalism.